An Anthropolinguistic Analysis of Cultural Values and Social Structure in the Traditional Songs Kampuang Nan Jauah di Mato and Furusato - Lestari, Imelda Indah; Putri, Darni Enzimar; Rumbardi, Rumbardi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Andalas, 2025)
This study examines the cultural values, worldview, and social structure embedded in the lyrics of two traditional songs: the Minangkabau song